Response of Different Insect Groups to Various Wavelengths of Light under Field Conditions - Hongsheng Pan; Gemei Liang; Yanhui Lu (Insects, 2021)
Insects in the same taxonomic group generally have similar responses to light at various wavelengths in the laboratory. However, there is lack of direct evidence of between-group differences in insect responses to various light wavelengths under field conditions. During 2014 and 2015, we evaluated the relative attractiveness of LEDs with 19 single wavelengths to three pest orders and four natural predator orders in cotton fields. The average numbers of Lepidoptera, Hemiptera, Coleoptera, and total pests captured by traps with a 395-nm LED wavelength were higher than those for all others, except 440-nm wavelength captured the largest number of Hemiptera in 2015. For natural enemies, the average numbers of Coleoptera, Neuroptera, and total natural enemies were the largest in traps with a 572-nm LED wavelength, except 538-nm wavelength captured the largest number of Coleoptera in 2014. In general, the ratio of pests to natural enemies captured in the 395-nm wavelength LED trap was significantly more than all others. These results demonstrated that insects in different taxonomic groups have significantly different responses to light at various wavelengths under field conditions; these results will provide insights for in-depth studies on insect phototaxis and guide the long-term monitoring of insects in different groups.